ANALISIS EFEKTIVITAS MESIN PRESS HYDRAULIC WIRE ROPE PADA PT TOBACON BATAM - Pardede, Anggi Angelina Br; Ganda Sirait (LPPM Universitas Putera Batam, 2024)
PT Tobacon is one of the distribution companies in Batam that offers quality and innovative coiling wire rope products to meet the needs of ship construction. The problem in this research is that the performance of the hydraulic wire rope press machine is not effective and the machine often experiences downtime, so that the output is not fulfilled. The purpose of this research is to analyze the factors that cause the ineffectiveness of the hydraulic wire rope press machine so that improvement recommendations can be determined on the hydraulic wire rope press machine. The method used in this research is Overall Equipment Effectiveness (OEE) to get the value of availability, performance efficiency and rate of quality. Based on the results of the study, it was found that the main factors affecting the OEE value of the Hydraulic Wire Rope Press machine were availability with an average of 84% and performance rate with an average of 88%, caused by the lack of regular machine checks which resulted in engine interference. Improvement recommendations suggested to increase effectiveness are Planned maintenance by scheduling maintenance according to machine conditions, creating maintenance standards for components and machines and providing training to operators. In addition, preventive maintenance is carried out by regularly maintaining the main components and providing lubrication to moving components to prevent component wear.